Workshops and distance education: completing an action in higher education in fashion (ModaPalavra e-periódico, 2009)
This study aimed to develop an experimental video lesson toVETL (AVEA) – virtual environment for teaching-learning to be offered in distance mode as na extra educational support to Experimental Manufacturing Atelier classes. This subject is part of the curricular guide in Fashion Bachelor course – Fashion Design at CEART/UDESC. It presentes concepts and characteristics of distance education, as well as a description of a system for management courses – Moodle, and the activity of infodesign. The video lesson was based on the methodology proposed by LigiaC.Girao and the main topic chosen was manufacturing a male shirt.
Keywords: higher education in fashion; video lesson; Moodle